FOREIGN EXCHANGE RESERVES OF INDIA IN RELATION WITH GDP (International Journal of Food and Nutritional Sciences, 2023)
This study examines“the relationship between India's foreign exchange reserves and Gross Domestic Product (GDP) over the past two decades. Foreign exchange reserves, managed by the Reserve Bank of India (RBI),” are vital for stabilizing the national currency, supporting monetary policy, and providing a buffer against economic crises. By analyzing historical data from 2000 to 2022, this study aims to understand how changes in reserves correlate with GDP fluctuations and what implications this has for India's economic strategy and stability.